The Roles of Adipose Tissue Macrophages in Human Disease - Liang, Weizheng; Qi, Yanxu; Yi, Hongyang; Mao, Chenyu; Meng, Qingxue; Wang, Hao; Zheng, Chunfu (Frontiers in Immunology, 2022)
Macrophages are a population of immune cells functioning in antigen presentation and inflammatory response. Research has demonstrated that macrophages belong to a cell lineage with strong plasticity, heterogeneity and can be polarized into different phenotypes under different microenvironments or stimuli. Many macrophages can be recruited by various cytokines secreted by adipose tissue. The recruited macrophages further secrete various inflammatory factors to act on adipocytes, and the interaction between the two leads to chronic inflammation. Previous studies have indicated that adipose tissue macrophages (ATMs) are closely related to metabolic diseases like obesity and diabetes. Here, we will not only conclude the current progress of factors affecting the polarization of adipose tissue macrophages but also elucidate the relationship between ATMs and human diseases. Furthermore, we will highlight its potential in preventing and treating metabolic diseases as immunotherapy targets.